Isolation and Nile Red screening of indigenous microalgae species from Pahang lakes as potential lipid source in aquaculture feed - Muhammad Faiz Zakaria,; Noorazilah Haris,; Mohd Effendy Abd Wahid,; Katayama, Tomoyo; Malinna Jusoh, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The high nutritional composition of microalgae that includes lipids is considered as one of the promising alternative lipid sources for animal feeds enrichment. Since microalgae have higher photosynthetic efficiencies than terrestrial plants, highly adaptable to environmental changes, and do not compete with conventional agriculture for resources, the inclusion of lipid sources from microalgae in feed could help the sustainability of livestock production systems. This study has reported the indigenous microalgae strains from Pahang lakes and determined lipid-rich strains that have the potential for alternative lipid sources. Pure isolated strains were identified using an 18S rDNA marker. The microalgae strain biomass was determined for 15 days. Meanwhile, the screening for high-rich lipid contents in microalgae strains was carried out using Nile Red fluorescent dye. A total of 11 strains were successfully isolated that consist of 8 different species (Carteria radiosa, Spongiosaccinopsis terrestris, Desmodesmus sp., Desmodesmus abundans, Dendodesmus brasiliensis, Chlamydomonas reinhardtii, Mychonastes timauensis, and Mychonastes ovahimbae). Results showed that PHG C01, PHG C02, and PHG F03 have the highest biomass production among all strains. Meanwhile, for lipid production, PHG B01 and PHG F03 showed the highest results. Thus, PHG B01 and PHG F03 strains were chosen as potential candidates to be used as an alternative lipid source in animal feed feedstock.